Peran Komunikasi Keluarga Terhadap Kesehatan Mental Anak Remaja di Desa Karae - Yanti, Yanti; Hidayatullah, Muhammad; Fida, Wa Nur (Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to find out the role of family communication on the mental health of teenagers in Karae Village. This research uses qualitative research methods with a descriptive research nature. In this research, the author collected data using observation, interviews, documentation and literature study techniques. From there, it is analyzed whether the functions of family communication are implemented in the family or not, whether they are successful or not, and what the shortcomings are. The results obtained are that family communication has been implemented, but according to the author there must be a specific form of family communication that is applied, namely the theory of heart communication. A communication that focuses on the importance of emotional relationships in the communication process, emphasizing that effective communication starts from positive thoughts and feelings.